Linguistic and Cultural Innovation in Schools The Languages Challenge - Spiro, Jane (Springer International Publishing, 2018)
This book presents case studies of five schools engaged in radical change in order to engage with children's home languages and cultures in a more multilingual and inclusive way. Located around the globe, from Hawaii to Kenya, the case studies are informed by both researchers and professionals on the ground. While the schools in question are each anchored in a unique context and situation, they also have a common mission to see language diversity as a resource, and a responsibility to embrace all the languages of their pupils. The authors offer a rich resource for education professionals and policymakers, including not only theoretical insights but useful practical tips. This innovative volume will be a helpful resource for educational professionals interested in following a path of multilingualism as well as students and scholars of second language acquisition, heritage languages and cultures and multilingual educational policy. Jane Spiro is Reader in Education and TESOL at Oxford Brookes University, UK. She has run projects for the development of international teachers and learners of English in four continents of the world. She has published widely on TESOL methodologies, teacher reflection, internationalisation and learner creativity. Eowyn Crisfield is a specialist in bilingualism and education. She works to bridge the divide between research and practice, supporting whole school communities to embed languages across the curriculum, and to develop policy and practices that empower language diversity. .